Competition drives the response of soil microbial diversity to increased grazing by vertebrate herbivores. Issue 7 (12th June 2017) - Eldridge, David J.; Delgado‐Baquerizo, Manuel; Travers, Samantha K.; Val, James; Oliver, Ian; Hamonts, Kelly; Singh, Brajesh K.
Abstract: Scientists have largely neglected the effects of grazing on soil microbial communities despite their importance as drivers of ecosystem functions and services. We hypothesized that changes in soil properties resulting from grazing regulate the diversity of soil microbes by releasing/suppressing subordinate microbial taxa via competition. To test this, we examined how intensity of vertebrate herbivores influences the diversity and composition of soil bacteria and fungi at 216 soil samples from 54 sites across four microsites. Increasing grazing intensity reduced soil carbon, suppressing the dominant bacterial phylum Actinobacteria (indirectly promoting bacterial diversity) and increasing the dominant fungal phylum Ascomycetes (indirectly reducing fungal diversity). Our data provide novel evidence that grazing modulates the diversity and composition of soil microbes via increases or reductions in competition by dominant taxa. Our results suggest that grazing can potentially alter soil function by altering microbial community composition, providing a clear link between grazing management, carbon availability and ecosystem functions.